The Brink of All We Hate : English Satires on Women, 1660-1750 - Nussbaum, Felicity (Book collections on Project MUSE., 1984)
Examining the elements of the tradition of antifeminist satire in the Restoration and eighteenth century, and exploring its uses, Nussbaum reveals a clearer context in which many poems of the period will be read anew.